2021
DOI: 10.3390/pharmaceutics13121991
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Therapeutic Drug Monitoring of Voriconazole, Mycophenolic Acid, and Vancomycin: A Literature Review of Pediatric Studies

Abstract: The review includes studies dated 2011–2021 presenting the newest information on voriconazole (VCZ), mycophenolic acid (MPA), and vancomycin (VAN) therapeutic drug monitoring (TDM) in children. The need of TDM in pediatric patients has been emphasized by providing the information on the differences in the drugs pharmacokinetics. TDM of VCZ should be mandatory for all pediatric patients with invasive fungal infections (IFIs). Wide inter- and intrapatient variability in VCZ pharmacokinetics cause achieving and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…Simulated results are displayed in Figure 5 . Based on the simulation results, the recommended dosing regimen for pediatric HSCT recipients to achieve a therapeutic target AUC 0–12 within the range of 30–60 mg·h/L was the oral administration of MMF at a dose of 900 mg/m 2 twice daily [ 11 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Simulated results are displayed in Figure 5 . Based on the simulation results, the recommended dosing regimen for pediatric HSCT recipients to achieve a therapeutic target AUC 0–12 within the range of 30–60 mg·h/L was the oral administration of MMF at a dose of 900 mg/m 2 twice daily [ 11 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, such adjustment is not an adequate substitute for therapeutic drug monitoring (TDM) because other factors (ie, liver function, drug interactions, the site of infection, and comorbidities) can also influence VRC exposure. [36][37][38][39][40] Therefore, dose adjustments should be combined with TDM to reduce the risk of adverse reactions. Furthermore, risk-benefit analysis should be performed in combination with the patient's actual situation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicated that dose adjustments should be based on CYP2C19 phenotype, body weight, and drug susceptibility testing. However, such adjustment is not an adequate substitute for therapeutic drug monitoring (TDM) because other factors (ie, liver function, drug interactions, the site of infection, and comorbidities) can also influence VRC exposure 36–40 . Therefore, dose adjustments should be combined with TDM to reduce the risk of adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Various organizations have laid down guidelines for TDM. Vancomycin is a glycopeptide antibiotic with an activity against Gram-positive bacteria [ 13 ], comprising the methicillin-resistant Staphylococcus aureus (MRSA). Vancomycin notoriously has a NTI [ 14 ].…”
Section: Discussionmentioning
confidence: 99%